Transformational Leadership as a Catalyst for Innovation and Operational Efficiency in the Insurance Industry - Azzaakiyyah, Hizbul Khootimah; Suherlan; Junaidi, Ahmad (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to examine the role of transformational leadership in improving the performance of insurance companies. Transformational leadership is known for its ability to inspire and motivate employees to achieve organisational goals, create positive change, and improve operational efficiency and customer satisfaction. Using a literature review approach and descriptive analysis, this study collected data from 28 articles published between 1999 and 2025 through Google Scholar sources. The results show that leaders who adopt a transformational leadership style are able to create an organisational culture that supports innovation and creativity, improves the quality of customer relationships, and drives overall performance improvement. The implication of this study shows that insurance companies need to pay attention to transformational leadership development to improve the competitiveness and sustainability of the company in a highly competitive industry. This research also provides suggestions for integrating leadership training and technology adoption in employee development strategies.